Two new species of the genus Nigrimacula (Orthoptera: Tettigoniidae: Meconematinae) from Yunnan, China - Duan, Yanhao; Guo, Qi; Shi, Fuming (Zootaxa, 2022)
The paper reports two new species of the genus Nigrimacula, i.e. Nigrimacula compressata sp. nov. and Nigrimacula platycerca sp. nov. Morphological illustrations and habitus photographs are provided. The type specimens are deposited in the Museum of Hebei University.